2010
DOI: 10.1097/tp.0b013e3181d9e195
|View full text |Cite
|
Sign up to set email alerts
|

Risk Score Predicting Decline in Renal Function Postliver Transplant: Role in Patient Selection for Combined Liver Kidney Transplantation

Abstract: This information will complement previously published criteria for CLKT patient selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…In a recent study by O'Riordan et al, a risk score was developed to predict a low GFR (Ͻ30 mL/min) at 1 year post-LTA. However, the numbers progressing to this level of function were small, and the score was also not able to predict the development of ESRD because this event was also low (14). In a study by Bahirwani et al (15), patients with increased serum creatinine for more than 12 weeks preliver transplant had a high risk (hazard ratio 5.3) of developing an estimated GFR less than 20 mL/min, but only 25% did so during a 3-year period.…”
Section: Discussionmentioning
confidence: 87%
“…In a recent study by O'Riordan et al, a risk score was developed to predict a low GFR (Ͻ30 mL/min) at 1 year post-LTA. However, the numbers progressing to this level of function were small, and the score was also not able to predict the development of ESRD because this event was also low (14). In a study by Bahirwani et al (15), patients with increased serum creatinine for more than 12 weeks preliver transplant had a high risk (hazard ratio 5.3) of developing an estimated GFR less than 20 mL/min, but only 25% did so during a 3-year period.…”
Section: Discussionmentioning
confidence: 87%
“…There has been a consensus that pre-transplant renal dysfunction was a strong predictor of poor prognosis after LT, especially in patients with high MELD score [15], [30], [31]. In some LT candidates with severe kidney impairment, renal function maybe deteriorated after LT and combined liver kidney transplantation should be considered [15], [32]. Our results were consistent with the previous studies that high prevalence of hepatorenal syndrome contributed to the high incidence of post-transplant acute kidney injury and high mortality.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 For example, investigators have used registration data to examine the decline in renal function after liver transplantation, and these risk prediction results have been validated and informed use of SLK transplant. [19][20][21][22] A recent decision analysis by Kiberd and colleagues 13 suggested that when both ESLD patients and ESRD patients are considered together, SLK transplantation does not maximize the total quality adjusted life years. Our study confirms that conclusion and extends Kiberd's results to identify the pretransplant dialysis duration threshold that provides the best balance of the net benefit or loss of life years for both ESLD and ESRD patients, thereby providing new data that can be used by decision makers when developing policies for equitable and effective allocation of scarce kidney grafts.…”
Section: Discussionmentioning
confidence: 99%